MENUMBUHKAN JIWA WIRAUSAHA GENERASI Z SEBAGAI UPAYA MENDORONG KEMANDIRIAN EKONOMI SISWA - Kealvin Nugraha; Ariyanto Ariyanto; Muhamad Aliyudin (LAP4B, 2026)
Generation Z is a generation that grows alongside the rapid development of digital technology, providing wide opportunities for self-development through various paths, including entrepreneurship. However, students' interest in and understanding of entrepreneurship remains relatively low, as their mindset tends to be oriented toward becoming job seekers rather than job creators, a tendency that mirrors the global pattern of rising youth NEET (Not in Employment, Education, or Training) rates. This Community Service Program aims to cultivate an entrepreneurial spirit among students of SMK Negeri 59 Jakarta as an effort to encourage economic independence from an early age, while also addressing the national urgency surrounding the persistently high unemployment rate among vocational school graduates in Indonesia. The activity was carried out using a qualitative descriptive approach through polite and participatory material presentation, interactive discussions, simple business plan simulations using the Business Model Canvas approach, and question-and-answer sessions. The materials covered basic entrepreneurship concepts, entrepreneurial characteristics and mindset, business opportunity identification, simple business model development, digital marketing strategies, and small business financial management. The results show an increase in participants' understanding of the importance of an entrepreneurial spirit, their ability to identify business opportunities in their surrounding environment, and their motivation to start small businesses as a foundation for economic independence. Participants also demonstrated strong enthusiasm in developing creative business ideas based on local potential and digital platforms, along with a growing awareness of basic financial literacy for business sustainability. It is expected that this program will help students build an entrepreneurial mindset, gain the courage to take calculated risks, and be prepared to face future economic challenges independently and sustainably.